2002
DOI: 10.1029/2001ja900113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for kinetic Alfvén waves and parallel electron energization at 4–6 RE altitudes in the plasma sheet boundary layer

Abstract: [1] We present evidence based on measurements from the Polar spacecraft for the existence of small-scale, large-amplitude kinetic Alfvén waves/spikes at the plasma sheet boundary layer (PSBL) at altitudes of 4-6 R E . These structures coincide with larger-scale Alfvénic waves that carry a large net Poynting flux along magnetic field lines toward the Earth. Both structures are typically observed in the PSBL but have also been observed deeper in the plasma sheet. The small-scale spikes have electric field amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
315
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(347 citation statements)
references
References 41 publications
31
315
0
1
Order By: Relevance
“…At higher altitudes where the warm plasma effects are important, Landau damping can lead to enhanced parallel electric fields that can accelerate auroral electrons, as in the observations of Wygant et al [2002]. The simulation results show that parallel electric field structures with scale sizes of a few tens of kilometers can result from this process, as observed by Knudsen et al [2001].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…At higher altitudes where the warm plasma effects are important, Landau damping can lead to enhanced parallel electric fields that can accelerate auroral electrons, as in the observations of Wygant et al [2002]. The simulation results show that parallel electric field structures with scale sizes of a few tens of kilometers can result from this process, as observed by Knudsen et al [2001].…”
Section: Discussionsupporting
confidence: 51%
“…The conversion of a fraction of this Poynting flux to electron fluxes was observed by Dombeck et al [2005] by comparing Polar and FAST data. Furthermore, Wygant et al [2002] observed the field-aligned acceleration of electrons at Polar in the 4-6 R E altitude range. These fieldaligned electrons had pitch angles within the loss cone, approximately 5°at Polar altitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They pointed out that the ability of an inertial Alfvén wave to accelerate electrons is well established theoretically, much less is known observationally. That is to say, the Alfvénic process has not been established observationally, though some case studies suggested auroral particle acceleration by the inertial or kinetic Alfvén wave [e.g., Wygant et al, 2002]. Wygant et al [2002] suggested that small-scale kinetic Alfvén waves are generated from the large-scale Alfvén wave structures.…”
Section: Akr Modulation and Global Pi2 Oscillationsmentioning
confidence: 99%
“…That is to say, the Alfvénic process has not been established observationally, though some case studies suggested auroral particle acceleration by the inertial or kinetic Alfvén wave [e.g., Wygant et al, 2002]. Wygant et al [2002] suggested that small-scale kinetic Alfvén waves are generated from the large-scale Alfvén wave structures. The midlatitude and high-latitude Pi2 of the present event exhibited the signature of the oscillating SCW (dB SCW ), which is considered as a manifestation of the Alfvénic perturbation of the field-aligned current (dj k ) along the auroral field line.…”
Section: Akr Modulation and Global Pi2 Oscillationsmentioning
confidence: 99%